(untitled) (TEL Tempo, Espaço e Linguagem, 2022)
This article aims to present a reflection on the historian’s craft, having as reference object the autobiography Meus Verdes Anos (1956) by José Lins do Rêgo. Our discussion started from some theoretical assumptions applied to the field of the theory of history, namely: the existence of the coloniality of knowledge, epistemic genocide and the place of speech. We aim to articulate some ideas from authors linked to the decolonial and postcolonial movement in order to reflect on the implications of the use of the work in question in the context of the criticism of the colonial way of structuring knowledge in historiography. Our primary intention was not to describe the person of José Lins do Rego, or to judge the usefulness of his memories. It was, above all, to situate the use of the literary man’s work in the context of a larger structure that will serve us as an interpretive key, this structure concerns the rules of knowledge production in the West, the epistemological assumptions that govern the practices of writing of the historians, issues that are often overlooked in Clio. We chose to limit the scope of our reflection to the use of the work in question, although the implications of this can obviously be broader.